(untitled) (Journal of the College of Education for Women, 2024)
This study, conducted as a quantitative analysis, aims to investigate how high school teaching methods impact the writing abilities of incoming freshmen at Tishreen University’s English Department in Latakia, Syria, and whether these students meet the Department’s standards. To achieve this, 60 writing samples from the Composition and Comprehension 1 exam in the first semester of the 2022-2023 academic year were gathered and analyzed for linguistic and meta-discourse markers. The analysis revealed that many students struggled with constructing coherent sentences, using appropriate vocabulary, and employing academic discourse markers. These findings emphasize the importance of improving the transition between educational stages by aligning teaching practices. To facilitate a smoother transition, it is crucial to implement effective writing exercises at the high school level. Such exercises provide students with opportunities to refine their composition skills, including grammar and vocabulary usage, which are essential for success in the English Department, particularly when tasked with producing longer English texts. In conclusion, this study highlights the significance of bridging the gap between high school and university writing, emphasizing the need for enhanced teaching practices at both levels to better prepare students for academic success in higher education. Accuracy